Analisis Kemampuan Shooting Menggunakan Punggung Kaki Pada Siswa Ekstrakurikuler Futsal Sma Negeri 5 Palopo - David Usman; Kahar, Irsan; Galugu, Nur Saqinah; Hidayat, Rachmat (Universitas Hamzanwadi, 2025)
The problem of this study is that the ability to shoot using the instep is not yet optimal, which is a crucial problem for futsal extracurricular students at SMA Negeri 5 Palopo. The purpose of this study is to analyze and describe specifically the level of ability to shoot using the instep in these students. This quantitative descriptive research method uses a survey approach. The sample consisted of 15 students, taken using total sampling technique. The research instrument was a shooting test from a distance of 10 meters to a standard futsal goal divided into nine scoring zones (1-5). The data were analyzed using descriptive statistics with the help of SPSS software. The results revealed a wide variation in ability. A total of 40% of students (6 people) were classified as “poor,” 20% (3 people) as “fair,” 33% (5 people) as “good,” and only 7% (1 person) as “very good.” The average score obtained was 12.93, which falls within the “fair” category. It was concluded that the ability to shoot using the instep among futsal extracurricular students at SMA Negeri 5 Palopo was generally still at a sufficient level and not yet optimal. These findings indicate the need for a more structured, intensive training program that focuses on improving basic techniques to increase shooting accuracy and power.